Food packaging materials testing & quality assurance - Singh, Preeti (CRC Press, 2017)
This book is arguably the first one focusing on packaging material testing and quality assurance. Food Packaging Materials: Testing & Quality Assurance provides information to help food scientists, polymer chemists, and packaging technologists find practical solutions to packaging defects and to develop innovative packaging materials for food products. Knowledge of packaging material testing procedures is extremely useful in the development of new packaging materials. Unique among books on packaging, this reference focuses on basic and practical approaches for testing packaging materials. A variety of packaging materials and technologies are being used, with glass, paper, metal, and plastics as the most important groups of materials. Material properties such as mechanical and other physical properties, permeability, sealing, and migration of substances upon food contact are determining factors for food quality, shelf life, and food safety. Therefore, food packaging materials have to be tested to ensure that they have correct properties in terms of permeability for gases, water vapor, and contaminants; of mechanical and other physical properties; and of the thickness of main components and coating layers.